PROFIL IBU RUMAH TANGGA USAHA WARUNG MAKANAN DAN MINUMAN DI DESA TUALANG, KECAMATAN TUALANG, KABUPATEN SIAK - Indah Febria Rahma; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted in Tualang Village, Tualang District, Siak Regency. This study aims to find out the profile of housewives who open food and beverage stall businesses and to find out the activities of housewives who open food and beverage stalls in carrying out family functions. This research is entitled “Profil Of Household Of Business Food And Beverages in Tualang Village, Tualang District, Siak Regency”. The main problem of this research is how are the characteristics of a housewife who opens a food and beverage stall business and how does the housewife carry out her business activities and carry out her family functions. Sample take in observational it is with Purposive Sampling tech. Total sample which is 27 person. Method that is utilized is kuantitatif's Descriptive method with kuantitatif's data analysis.Data winnow instrument that is utilized is observation, giuded interview and documentation. Observational result in common that is done therefore researcher concludes: Profile of housewives who open food and beverage stalls is a group of housewives aged 25-30 years, most of whom open breakfast shops. Besides running food and beverage stalls, the housewife can still do joint activities family such as: gathering with family, eating with family, praying together with family, accompanying and helping children to do homework, and paying attention to children and husbands.  Keywords: Informal Sector, Family, Housewife